The Heart of the Flats - February, Bronwyn (Open Mic: A Creative Writing Journal, 2024)
The poem"The Heart of the Flats" by Bronwyn February describes the author’s journey as a youth development worker in the Cape Flats area of South Africa. The author highlights how daily communal struggles are overcome with resilience and the gift of being an empathetic leader who plants seeds of change, hope, and peace.